2019
DOI: 10.1007/s10551-019-04148-1
|View full text |Cite
|
Sign up to set email alerts
|

Private Sector Corruption, Public Sector Corruption and the Organizational Structure of Foreign Subsidiaries

Abstract: Corporate anti-corruption initiatives can make a substantial contribution towards curtailing corruption and advancing efforts to achieve the United Nations' Sustainable Development Goals. However, researchers have observed that underdeveloped assumptions with respect to the conceptualization of corruption and how firms respond to corruption risk impeding the efficacy of anti-corruption programs. We investigate the relationship between the perceived level of corruption in foreign host countries and the organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 154 publications
(169 reference statements)
1
42
1
5
Order By: Relevance
“…Corruption has been identified as one of the significant components hindering sustainable development affecting the public and private sector (Frolova et al 2019;Sartor and Beamish 2019), peace and security (Basabose 2019). It negatively impacts trust in government, contributes to social inequality and poverty.…”
Section: Combating Corruptionmentioning
confidence: 99%
“…Corruption has been identified as one of the significant components hindering sustainable development affecting the public and private sector (Frolova et al 2019;Sartor and Beamish 2019), peace and security (Basabose 2019). It negatively impacts trust in government, contributes to social inequality and poverty.…”
Section: Combating Corruptionmentioning
confidence: 99%
“…This definition has gained great popularity and is also found in international anti-corruption conventions (for example, in the UN Convention against Corruption, Council of Europe documents, etc.). However, in recent years, more and more attention has been paid to corruption in the private sphere, as its size and negative effects are becoming more significant and cannot be neglected (Argandoña, 2003;Gopinath, 2008;Stoyanov, 2018;Sartor, & Beamish, 2020).…”
Section: Manifestations Of Corruption In Contemporary Societymentioning
confidence: 99%
“…Corruption does not only happen in public sector but also in private sector because it is a deliberate action to provide fraud over particular amount on the financial report in order to decrease credibility of its report (Umar, 2012). Researchers whose work has focused on combatting corruption within NGOs have observed that prevalent forms of abuse of power (or, corruption) within this type of private sector organization include the establishment of "fictitious NGOs" solely for the purpose of generating income for the organization's executives or Board members, the receipt of kickback payments by NGO employees from prospective vendors with respect to the procurement of goods or services for the organization, and the solicitation of bribes by NGO employees from prospective beneficiaries who seek inclu-sion on NGO aid distribution lists (Sartor & Beamish, 2018). After initial skepticism, companies worldwide are now adopting programs to combat corruption.…”
Section: Anti-corruption In Private Sectormentioning
confidence: 99%